Kekuatan Kelompok Keagamaan sebagai Alat Kepentingan Aktor Politik Lokal pada Pilkada 2024 di Kota Pematangsiantar (Studi Kasus Naposobulung HKBP Siantar Timur Ressort Siantar Timur): The Power of Religious Groups as a Tool for Local Political Actors in the 2024 Regional Elections in Pematangsiantar City (Case Study Naposobulung HKBP Siantar Timur Ressort Siantar Timur) - Agatha Dwi Natania Panjaitan; Faisal Andri Mahrawa (Litera Academica Publishing, 2026)
This research examines how the strength of Naposobulung HKBP as a religious group is used as a tool for interests by local political actors in the 2024 Pematangsiantar City elections. This research aims to describe the mechanisms, motivations, and impacts of utilizing Naposobulung as a political tool. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The research results show that local political actors implement various strategies both symbolically and materially based on the Dalihan na Tolu philosophy to gain moral legitimacy and cultural solidarity from Naposobulung. Political actors utilize church social networks, diaconal activities, and community values to build voter loyalty, while youth groups experience an increase in social roles along with the risk of religious politicization. However, in the 2024 regional elections, there was a significant decline in the practical role of Naposobulung due to weak internal consolidation and the church leaders' stance of limiting political activities, although the cultural solidarity values based on the Dalihan na Tolu philosophy were still preserved. The socio-religious potential of this group has not been completely lost; with the reorganization of functions, strengthening of internal coordination, and the opening of political dialogue spaces by church leaders, Naposobulung can once again support participatory democracy. Recommendations include adapting mobilization strategies, enhancing political literacy among youth, and formulating internal church policies that balance religious roles and democratic interests.